Superficial Musculoaponeurotic System Flap for Reconstruction of the Intraoral Defects - DURMUŞ KOCAASLAN, FATMA NİHAL; ÇELEBİLER, ÖZHAN BEKİR; AKDENİZ DOĞAN, ZEYNEP DENİZ (THIEME MEDICAL PUBL INC, 2013)
Intraoral tumors are the main causes of the intraoral and maxillofacial defects. Skin grafts and several soft tissue flaps can be used to reconstruct the intraoral defects including local, regional, and free flaps. Here we present a case of intraoral adenocystic carcinoma treated with segmental maxillectomy, resection of the parotid gland, and the buccal mucosa leaving a full-thickness intraoral defect. The defect was covered with a superficial musculoaponeurotic system (SMAS) flap elevated using the preauricular incision. Reconstruction with SMAS flap for temporal defects and parotidectomy defects has been described in the literature. To our knowledge, the use of this flap for intraoral defects has not been reported. The proximity of the flap to the defect and ease of harvest in cases including total parotidectomy are few of the reasons we use and recommend this flap in reconstruction of intraoral defects.
Keywords: intraoral defect; SMAS; reconstruction